The city and the citizen: for a political-territorial approach to the concept of citizenship from an emancipatory perspective - Raique Lucas de Jesus Correia; Waldemar Almeida de Oliveira Filho; José Euclimar Xavier de Menezes (Geografares, 2024)
This article proposes an analysis of the concept of citizenship based on a territorial anchoring that highlights an articulating perspective between Law and Geography. Through exploratory research, it seeks to shift the discussion of citizenship as a legal-normative category to conceive it within a broader political framework, grounded in territorial-based struggles and social movements of resistance. The journey begins by locating the forms of understanding citizenship in different periods of Western history, analyzing the changes, continuities, and contradictions that have established themselves over time. After that, the relationship between citizenship and territory is discussed, invoking the territorial component as the material content of the exercise of citizenship itself. Finally, it seeks to link the concept of citizenship to the notion of territorial resistance, primarily from a critical perspective of the constituent power of Human Rights. In conclusion, it affirms the importance of insurgent movements and territorial dynamics in the processes of realizing citizens’ rights and human emancipation.